Analisis Faktor yang Mempengaruhi Preferensi Penggunaan QRIS sebagai Alat Pembayaran pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Riau - Rahmadani, Shella Maidi; Syapsan, Syapsan; Widayatsari, Any (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to determine the influence of knowledge, perceived usefulness, and perceived security on students’ preference to use QRIS at the Faculty of Economics and Business, University of Riau. The research employed a quantitative method with 100 respondents selected using proportional random sampling. Data were analyzed using multiple linear regression. The results indicate that knowledge, usefulness, and security have a positive and significant influence, both partially and simultaneously, on students’ preference to use QRIS. These findings show that higher levels of knowledge and perceived benefits, along with well-managed perceived risks, increase students’ preference toward QRIS usage.